Ernst Toller - Facetten eines schriftstellerischen Werks zwischen den Weltkriegen. Eine motivorientierte Untersuchung - Bigeard, Simone (KIT Scientific Publishing, 2018)
The analysis at hand is tracing a major literary strategy within Ernst Toller?s (1893-1939) œuvre, a strategy operating on the level of motif. Related motifs become part of a process that is best described as parallelization. The analysis focuses on the genesis and intricate structure of the complexes of motif "theatrum mundi", "doppelgänger", "masses/leader". Its major goal is to establish new impulses for further research into the literary techniques which are structuring Ernst Toller?s œuvre.